2009
DOI: 10.3389/neuro.08.001.2009
|View full text |Cite
|
Sign up to set email alerts
|

A trans-dimensional approach to the behavioral aspects of depression

Abstract: Depression, a complex mood disorder, displays high comorbidity with anxiety and cognitive disorders. To establish the extent of inter-dependence between these behavioral domains, we here undertook a systematic analysis to establish interactions between mood [assessed with the forced-swimming (FST) and sucrose consumption tests (SCT)], anxiety [elevated-plus maze (EPM) and novelty suppressed feeding (NSF) tests] and cognition (spatial memory and behavioral flexibility tests) in rats exposed to unpredictable chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
250
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(274 citation statements)
references
References 42 publications
18
250
1
5
Order By: Relevance
“…Exposure to stressful conditions induces depressive behavior and memory deficits in both rodents and humans (4)(5)(6)(7)(8). Studies in rodents have shown that chronic stress triggers Tau hyperphosphorylation, a key pathogenic mechanism in AD, and results in cognitive and mood deficits (9-13); however, those studies do not provide direct evidence for a role of Tau in stress-evoked brain pathology.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Exposure to stressful conditions induces depressive behavior and memory deficits in both rodents and humans (4)(5)(6)(7)(8). Studies in rodents have shown that chronic stress triggers Tau hyperphosphorylation, a key pathogenic mechanism in AD, and results in cognitive and mood deficits (9-13); however, those studies do not provide direct evidence for a role of Tau in stress-evoked brain pathology.…”
mentioning
confidence: 73%
“…Cognition, mood, and anxiety are interdependent behavioral domains that exhibit complex interactions (5). Different forms of memory were assessed after exposure of WT and Tau-KO mice to the CUS paradigm; the test battery included the Y-maze, Morris water maze (MWM), and the novel object recognition test (NOR).…”
Section: Deleterious Effects Of Stress On Memory and Mood Are Abrogatmentioning
confidence: 99%
“…Finally, Bessa et al (2009a) demonstrated that reduction of adult neurogenesis in rats did not change the effectiveness of several ADs in both FST and sucrose preference test, while their efficacy was blocked in NSF. This observation added to the notion that NSF shows anxiolytic rather than antidepressant properties of investigated drugs (discussed in Bessa et al, 2009a;Bessa et al, 2009b;David et al, 2009). Finally, the prevailing perception in the literature, suggests FST to be a proper test to show neurogenesis-dependence of antidepressant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our earlier study, no correlations were obtained between anxiety-and depression-related behaviours in WKY [17] , hinting at a probable separation of anxiety-and depression-related symptoms [23] . Core symptoms such as anhedonia and learned helplessness are not specific even in humans [24] .…”
mentioning
confidence: 99%